Impacts of the COVID-19 pandemic on elderly and adopted rehabilitation clinics (Research, Society and Development, 2021)
Introduction: The world is currently facing a pandemic that has changed the lifestyle of the population in general and generated consequences for the economy and public health, given the potential spread of the pathogen, SARS-CoV-2, which causes the disease COVID- 19. People over 60 years of age were identified as one of the most vulnerable groups to develop the severe form of the disease. The aim of this study was to verify in the literature the impacts of the COVID-19 pandemic on the elderly and the rehabilitation strategies that have been adopted in this period. Methodology: This was an integrative review that used articles indexed in Medline, PubMed and Scielo databases published between the years 2020 and 2021 in English, Portuguese and Spanish. Results: The COVID-19 pandemic and social isolation brought some health problems to the elderly. The articles analyzed in this review listed some of these disorders, including impaired motor function, impairment in performing activities of daily living, weakness acquired in the ICU and worsening of frailty. Final Considerations: The health of the elderly in the current scenario demands more specific attention that seeks to emphasize not only recovery, but also the prevention of these health problems. Furthermore, strategies to achieve these goals should be further studied in order to find methods to provide quality care to this population during and post-pandemic.